Pocket-size point-of-care ultrasound in rural Uganda — A unique opportunity "to see", where no imaging facilities are available. Issue 23 (May 2018) - Epstein, Danny; Petersiel, Neta; Klein, Erez; Marcusohn, Erez; Aviran, Eyal; Harel, Reut; Azzam, Zaher S.; Neuberger, Ami; Fuchs, Lior
Abstract: Background: In the developing world, only a small minority of patients have access to radiological services. Over the past decade, technological developments of ultrasound equipment have led to the emergence of point-of-care ultrasonography (POCUS), which is widely used by healthcare professionals of nearly all specialties. We hypothesized that physicians with only basic POCUS training, but with telemedicine support, can use POCUS successfully in rural hospitals in sub-Saharan Africa. Method: During a 14-day voluntary clinical work session in a rural hospital in central Uganda, bedside ultrasound scans were performed by use of a pocket-size portable machine by a physician who underwent a five-day training period. All the POCUS studies were reviewed by radiologists and cardiologists abroad with the use of telemedicine. Results: During the study period, 30% of patients received a POCUS-augmented physical examination. 16 out of 23 patients (70%) had positive findings; in 20 of them (87%), the management was changed. The technique was successfully used on trauma casualties, patients suffering from shock, patients with cardiorespiratory symptoms, and patients undergoing invasive procedures. Conclusions: In a very resource-limited environment, POCUS conducted by basically trained primary care physicians with telemedicine support is a powerful diagnostic tool in a variety of medical conditions.